Functionalized Bioadsorbent Application on Methylene Blue Removal From Wastewater—A Review - Jean B. Batchamen Mougnol; Sudesh Rathilal (Advances in Materials Science and Engineering)
There are many pollutants present in wastewater that require urgent remediation. Methylene blue (MB) has become the most undesirable pollutant. Various industries such as petroleum, pharmaceuticals, textiles and households have been responsible for releasing MB into the environment. Its toxicity and acute health implications for animals and humans have suggested several technological applications for its removal. Biological methods using plant-based wastes have been identified to be the most effective material for removing MB and other dye pollutants. Previous research studies have employed biological adsorbents to eliminate MB and were reviewed. The purpose of the study was to determine the removal efficiency gap of MB using biological wastes. In this present review, various biological wastes and their functionalization were explored. The study proved that chemically modified bioadsorbents were favourable in removing MB. Its ability to produce secondary pollutants from chemical agents has made it undesirable. Several factors such as pH, dosage of catalyst, contact time and temperature have also been reviewed to influence biosorption. The best data representations to describe the biosorption of MB were the Langmuir and pseudo-second-order models.